Abundant Z-cyanomethanimine in the interstellar medium: paving the way to the synthesis of adenine. (4th December 2018) - Rivilla, V M; Martín-Pintado, J; Jiménez-Serra, I; Zeng, S; Martín, S; Armijos-Abendaño, J; Requena-Torres, M A; Aladro, R; Riquelme, D
ABSTRACT: We report the first detection in the interstellar medium (ISM) of the Z-isomer of cyanomethanimine (HNCHCN), an HCN dimer proposed as precursor of adenine. We identified six transitions of Z-cyanomethanimine, along with five transitions of E-cyanomethanimine, using IRAM 30m observations towards the Galactic Centre quiescent molecular cloud G + 0.693. The Z-isomer has a column density of (2.0 ± 0.6) × 10 14 cm −2 and an abundance of 1.5 × 10 −9 . The relative abundance ratio between the isomers is [Z/E]∼6. This value cannot be explained by the two chemical formation routes previously proposed (gas phase and grain surface), which predicts abundances ratios between 0.9 and 1.5. The observed [Z/E] ratio is in good agreement with thermodynamic equilibrium at the gas kinetic temperature (130−210 K). Since isomerization is not possible in the ISM, the two species may be formed at high temperature. New chemical models, including surface chemistry on dust grains and gas-phase reactions, should be explored to explain our findings. Whatever the formation mechanism, the high abundance of Z-HNCHCN shows that precursors of adenine are efficiently formed in the ISM.